Design the whole story - Wilhide, Elizabeth (Thames & Hudson, 2016)
"Design: the whole story takes a close look at the key developments, movements and practitioners of design around the world, from the beginning of industrial manufacturing to the present day. Organized chronologically, and exploring key pieces and design milestones in depth, the book locates design within its varying technological, cultural, economic, aesthetic and theoretical contexts. From the high-minded moralists of the nineteenth century to the radical thinkers of modernism, from the emergence of showmen such as Raymond Loewy in the 1930s to today's superstars such as Philippe Starck, this book gets to the heart of design and the ways in which it touches all our lives." -- Provided by publisher.